Apartment Management Model: A Comparative Study between Pekunden Semarang and Singapore Rusunawa - Raphael Bertrand Mayaka; Baidhowi Baidhowi (Law Research Review Quarterly, 2025)
Flats are essential infrastructure designed for various purposes, including providing adequate housing for low-income communities. However, policy implementation has yet to be fully effective, as shown by the Pekunden Public Rental Flats (Rusunawa Pekunden) in Semarang, which face issues such as the absence of targeted government policies to address stagnant living patterns of low-income residents and weak management structures. This study aims to: (1) examine the penetration of Singapore’s Housing and Development Board (HDB) Ethnic Integration Policy into Indonesia’s public housing regulations; And (2) analyze the application of Singapore’s housing concepts and policies to improve the effectiveness of flat management in Indonesia. This qualitative research adopts a literature review approach to explore concepts, regulations, and best practices in housing management. The findings indicate that socio-economic segregation can be mitigated through regulatory reforms, including requiring at least 20% of commercial flat floor area to be allocated to low-income residents within the same development. Moreover, adopting HDB principles highlights the importance of centralized management, transparent financing, and social integration policies. In conclusion, strengthening regulations, innovating financing mechanisms, and promoting community participation are key strategies for creating effective, inclusive, and sustainable vertical housing that meets Indonesia’s urban development needs.